Staphylococcus aureus Depends on Eap Proteins for Preventing Degradation of Its Phenol-Soluble Modulin Toxins by Neutrophil Serine Proteases - Kretschmer, Dorothee; Breitmeyer, Ricarda; Gekeler, Cordula; Lebtig, Marco; Schlatterer, Katja; Nega, Mulugeta; Stahl, Mark; Stapels, Daphne; Rooijakkers, Suzan; Peschel, Andreas (Frontiers in Immunology, 2021)
Neutrophil granulocytes act as a first line of defense against pathogenic staphylococci. However, Staphylococcus aureus has a remarkable capacity to survive neutrophil killing, which distinguishes it from the less-pathogenic Staphylococcus epidermidis. Both species release phenol-soluble modulin (PSM) toxins, which activate the neutrophil formyl-peptide receptor 2 (FPR2) to promote neutrophil influx and phagocytosis, and which disrupt neutrophils or their phagosomal membranes at high concentrations. We show here that the neutrophil serine proteases (NSPs) neutrophil elastase, cathepsin G and proteinase 3, which are released into the extracellular space or the phagosome upon neutrophil FPR2 stimulation, effectively degrade PSMs thereby preventing their capacity to activate and destroy neutrophils. Notable, S. aureus, but not S. epidermidis, secretes potent NSP-inhibitory proteins, Eap, EapH1, EapH2, which prevented the degradation of PSMs by NSPs. Accordingly, a S. aureus mutant lacking all three NSP inhibitory proteins was less effective in activating and destroying neutrophils and it survived less well in the presence of neutrophils than the parental strain. We show that Eap proteins promote pathology via PSM-mediated FPR2 activation since murine intraperitoneal infection with the S. aureus parental but not with the NSP inhibitors mutant strain, led to a significantly higher bacterial load in the peritoneum and kidneys of mFpr2-/- compared to wild-type mice. These data demonstrate that NSPs can very effectively detoxify some of the most potent staphylococcal toxins and that the prominent human pathogen S. aureus has developed efficient inhibitors to preserve PSM functions. Preventing PSM degradation during infection represents an important survival strategy to ensure FPR2 activation.